Skewed Perceptions: Psychopathy and Systematic Biases of Risk and Reward from Adolescence to Emerging Adulthood - Altikriti, Sultan (Journal of developmental and life-course criminology, 2020)
Scholarship on perceptions of risk and reward of criminal behavior illustrates a substantial impact of individual differences on the decision to offend given a perceived opportunity. The current study extends this literature with a longitudinal assessment of the systematic effects of psychopathic personality traits on perceptions of offending., Multivariate regression analyses using a sample of adjudicated delinquents from the Pathways to Desistance study (n = 987) were employed to estimate the association between psychopathic personality traits and perceptions of offending in adolescence and emerging adulthood., Results indicated that individuals who scored higher on psychopathic personality traits reported higher perceptions conducive to crime in both adolescence and emerging adulthood., Identifying personality characteristics that affect perceptions of offending has important implications for deterrence and other criminological theories that rely on the perceptions of risk. The current study identified psychopathic personality traits as one source of individual differences in perceptions.